BANK’S LEGAL LIABILITY FOR STANDARD CLAUSES IN APARTMENT OWNERSHIP CREDIT AGREEMENTS FOR UNBUILT APARTMENTS - Tri Sufitri; Wulan Windiarti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
The growing development of apartments through the pre-project selling scheme has expanded public access to home ownership through Apartment Ownership Credit. However, this scheme also gives rise to legal problems when a project remains unbuilt or fails to be completed, while consumers remain obliged to continue paying their instalments to the bank. This study aims to analyze the application of standard clauses in KPA agreements for apartment projects that have not yet been built, and to examine the legal liability of conventional banks for losses suffered by consumers. This research employs a normative juridical method using statutory, conceptual, and case-based approaches. The findings show that standard clauses have the potential to place consumers in an unbalanced position, as they shift construction risk onto consumers. Such a practice is inconsistent with the principle of contractual balance, the principle of good faith, and Article 18 of Law Number 8 of 1999 on Consumer Protection. Banks remain responsible for applying the principles of prudence, transparency, and consumer protection in both the drafting and the implementation of credit agreements.